Simon Killer - Jurriaans, Saunder 1977-; Bensi, Danny ca. 20. Jh (Eureka entertainment ltd., 2013)
"Antonio Campo's astonishing porträt of a young and dislocated American as he hurtles through modern-day Paris at a destruction clip." [Cover]
Bildformat 2.40:1 original aspect ratio
Original: USA, Frankreich
Progressive transfer of the film in its origin aspect ratio ; optional english subtitles (SDH also available) ; "The last 15" - a 16-minute short film by Antonio Campos from 2006 ; the case of the conscious camera ; a 29-minute interview with Campos on the aesthetics of "Simon Killer" - Sundance alumni spotlight ; an interview with Campos, Sean Durkin, and Josh Mond conversations with Moms ; an interview with Campos, Brady Corbet, and their mothers ; a selection of behind-the-scenes and rehearsal footage featuring alternate takes ; original theatrical trailer ; 52-page booklet featuring a new and exclusive essay by critic Karina Longworth; a new interview with Antonio Campos ; alternate poster artwork
Keywords: Film; DVD-Video